Đào tạo nguồn nhân lực đáp ứng vị trí công việc tại doanh nghiệp thời kỳ chuyển đổi số - Nguyễn Quốc, Hùng; Nguyễn Thị, Hằng; Nguyễn Duy, Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The training of human resources with full background, specialized knowledge and career skills, teamwork skills, adaptation to the digital transformation context, and the development of businesses is the right direction, inevitably and objectively. The article uses survey methods, collecting expert opinions to collect actual data and form a scale. On that basis, analyze the reliability of the scale and factor analysis, test the hypotheses raised in the research. The research results have formed a theoretical scale to assess the ability of students to meet the employment needs of students in current businesses. At the same time, helping universities to adjust training content and methods to improve the quality of human resources to serve the development of digital businesses in the current digital transformation context.